Two new species of South Asian Cnemaspis Strauch, 1887 (Squamata: Gekkonidae) from the far northern peaks of the Western Ghats, India - Khandekar, Akshay; Thackeray, Tejas; Agarwal, Ishan; Gangalmale, Satpal; Kininge, Saurabh; Gaikwad, Sunil M. (Zootaxa, 2024)
We describe two new species of South Asian Cnemaspis from far northern peaks of the Northern Western Ghats of Maharashtra, India. The two new species are the most northernly distributed representatives of the girii clade and are phylogenetically and morphologically allied to C. uttaraghati. The new species are 15.0% divergent from C. uttaraghati in pairwise uncorrected ND2 sequence data, 9.9 % from each other, and over 17.5–18.8% from other members of the girii clade. The two new species can easily be distinguished from most members of the girii clade by a combination of non-overlapping morphological characters such as body size (maximum snout to vent length 35–43 mm), low number of dorsal tubercle rows (6–11), having irregular paravertebral tubercles, and high subdigital lamellae counts; and from each other and C. uttaraghati by the number of midventral scales across belly, the number of subdigital lamellae, and the number of poreless scales separating series of femoral pores. The new species and C. uttaraghati are distributed within 10–25 km of each other, providing an example of extreme micro-endemism in the Northern Western Ghats.